2017
DOI: 10.1007/s00300-017-2181-5
|View full text |Cite
|
Sign up to set email alerts
|

Declining health status of Brown Skua (Stercorarius antarcticus lonnbergi) parents and their offspring during chick development

Abstract: During breeding, Brown Skuas (Stercorarius antarcticus lonnbergi) perform a great physical effort in the care and maintenance of the nest. Interestingly, the breeding colony on which this work was conducted is in steady decline in recent years. In order to understand the physiological background responsible for the trade off between reproductive effort and health status, in adults and the possible reasons for the colony decline, we evaluated the health status in Brown Skuas parents and growing chicks and blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Once fat stores have been exhausted, protein utilization increases. Previous works revealed that when lipid stores are low, Brown Skuas shift towards protein catabolism to meet their energy requirements (Graña ) which has been demonstrated in other studies as well (Ibañez et al 2018). The induction of protein catabolism could indicate that female skuas were in 1 3…”
Section: Serum Lipoproteins During Reproductionmentioning
confidence: 71%
See 3 more Smart Citations
“…Once fat stores have been exhausted, protein utilization increases. Previous works revealed that when lipid stores are low, Brown Skuas shift towards protein catabolism to meet their energy requirements (Graña ) which has been demonstrated in other studies as well (Ibañez et al 2018). The induction of protein catabolism could indicate that female skuas were in 1 3…”
Section: Serum Lipoproteins During Reproductionmentioning
confidence: 71%
“…Three reproductive stages were defined: egg incubation (In), early rearing (Er) and late rearing (Lr) (Fig. 1) (Graña Ibañez et al 2018). For In, sampling was done during incubation of eggs.…”
Section: Sampling Site and Sample Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adults with a better body condition will possibly have more resources to be reallocated to avoid oxidative damage. It was previously described for breeding Brown Skuas during the intensive care of chicks that body mass and overall nutritional status decline because of the parental effort (Ibañez et al 2018;Graña Grilli et al 2018). During these breeding activities, a trade-off between oxidative stress damage and other physiological functions occur.…”
Section: Discussionmentioning
confidence: 99%